PENGUJIAN MODEL PORTOFOLIO BALANCE MODELS DALAM MENJELASKAN NILAI TUKAR RUPIAH - Santosa, Agus Budi (Proceeding SENDI_U, 2015)
This research aimed to test and analyze portfolio balance approach model (PBA) in explaining Rupiah exchangerate behavior to US Dollar. Based on empirical evidence, PBA model was used for the ability in predicting andexplaining exchange rate behavior. Whereas, ordinary least square (OLS) was chosen as analysis tool for the abilityto explain exchange rate behavior well. In short term period, portfolio equilibrium explained the allocation of somestock from wealth between securities alternative with expected basic result and exchange rate. Shock in portfolioequilibrium was assumed asbeingeliminatedwith prompt adaptation from exchange rate and interest rate. Thus, thewealth owner produced accurately equal request with offer from constant short term financial demand.The result ofthe research showed that price variable didnât influence Rupiah exchange rate to US Dollar significantly in shortterm, whereas, national income variable, the amount of circulated money, and Foreign Exchange Reservesinfluenced Rupiah exchange rate fluctuation to US Dollar. The using of PBA model as Rupiah exchange ratestabilization policy recommended a good Foreign Exchange Reserves management. The estimation result of BPAmodel with error correction showed significant OLS (ordinary least square)value, therefore, it was concluded thatthe model was validKeyword : portfolio balance models, stock, Foreign Exchange Reserves, portfolio quilibrium